21-O-Angeloyltheasapogenol E3, a Novel Triterpenoid Saponin from the Seeds of Tea Plants, Inhibits Macrophage-Mediated Inflammatory Responses in a NF-κB-Dependent Manner. (9th November 2014) - Yang, Woo Seok; Ko, Jaeyoung; Kim, Eunji; Kim, Ji Hye; Park, Jae Gwang; Sung, Nak Yoon; Kim, Han Gyung; Yang, Sungjae; Rho, Ho Sik; Hong, Yong Deog; Shin, Song Seok; Cho, Jae Youl
Abstract : 21-O-Angeloyltheasapogenol E3 (ATS-E3) is a triterpenoid saponin recently isolated from the seeds of the tea tree Camellia sinensis (L.) O. Kuntze. ATS-E3 has several beneficial properties including anti-inflammatory, antidiabetic, antiatherosclerotic, and anticancer effects. Unlike other phenolic compounds isolated from tea plants, there are no studies reporting the pharmacological action of ATS-E3. In this study, we therefore aimed to explore the cellular and molecular inhibitory activities of ATS-E3 in macrophage-mediated inflammatory responses. ATS-E3 remarkably diminished cellular responses of macrophages such as FITC-dextran-induced phagocytic uptake, sodium nitroprusside- (SNP-) induced radical generation, and LPS-induced nitric oxide (NO) production. Analysis of its molecular activity showed that this compound significantly suppressed the expression of inducible NO synthase (iNOS), nuclear translocation of nuclear factor- (NF-) κ B subunits (p50 and p65), phosphorylation of inhibitor of κ B kinase (IKK), and the enzyme activity of AKT1. Taken together, the novel triterpenoid saponin compound ATS-E3 contributes to the beneficial effects of tea plants by exerting anti-inflammatory and antioxidative activities in an AKT/IKK/NF- κ B-dependent manner.